Mixed convection heat transfer in power law fluids over a moving conveyor along an inclined plate. (June 2015) - Sui, Jize; Zheng, Liancun; Zhang, Xinxin; Chen, Goong
Abstract: We study the mixed convection boundary layer heat transfer of power law fluid over a moving conveyor along an inclined plate. The effects of shear flow and power law viscosity on the temperature field are taken into account according to a modified Fourier law. Approximate analytical solutions are obtained by the homotopy analysis method (HAM). Results indicate that heat transfer is strongly dependent on the values of power law exponent, inclination angle, boundary velocity ratio and Prandtl number. Three distinct characteristics are found for power law exponents 0 <  n  < 1, n  = 1 and n  > 1, especially the nonlinear behavior due to skin friction and local Nusselt number shown in Figs. 4 and 17, which has never been reported before. The decrease of inclination angle causes the loss of velocity boundary layer but the gain of temperature boundary layer. Heat transfer efficiency is enhanced but skin friction is diminished with the increase in velocity ratio (the ratio of conveyor velocity/mean velocity of flow field). Critical ratio (with skin friction zero) is obtained which strongly depends on the power law exponent. The effects of involved parameters on the velocity and temperature fields are analyzed.